2015
DOI: 10.1016/j.ijppaw.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of taeniids of wolves in Liguria (northern Italy)

Abstract: HighlightsWolves are considered as definitive hosts for Echinococcus granulosus in Liguria, Italy.Scats were examinated and taeniid eggs isolated.Molecular species identification was performed through PCR analysis and sequencing.Taeniid species diagnosed document domestic, semi-domestic and wildlife cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 38 publications
1
47
2
Order By: Relevance
“…To date, no information relating the prevalence of echinococcosis in sheep and cattle of the Park are available. However, the lower detection rate observed in this study, compared with what was reported by others (Gori et al 2015;Poglayen et al 2017), suggests a low prevalence of the parasite in livestock inhabiting the same area of the wolfs' pack. In addition, the wild boar, as a contamination source for echinococcosis in wild carnivores, could not be ruled out.…”
Section: Discussioncontrasting
confidence: 85%
“…To date, no information relating the prevalence of echinococcosis in sheep and cattle of the Park are available. However, the lower detection rate observed in this study, compared with what was reported by others (Gori et al 2015;Poglayen et al 2017), suggests a low prevalence of the parasite in livestock inhabiting the same area of the wolfs' pack. In addition, the wild boar, as a contamination source for echinococcosis in wild carnivores, could not be ruled out.…”
Section: Discussioncontrasting
confidence: 85%
“…The old faecal samples collected in the wild environment did not allow the individual animal identification and it cannot exclude that some faecal samples belonged to the same animal. Therefore, this study used the term frequency and not prevalence to describe the proportion of T. cati infections in the wild Amur tiger population investigated [46]. The Pnorm function was used to calculate the significant differences in frequency (%), and 95% confidence interval (CI) was calculated in PropCIs function in R version 3.5.2.…”
Section: Discussionmentioning
confidence: 99%
“…Guberti et al (2004) reported a prevalence of 15% for this parasite in 119 wolves from the Italian Apennines and suggested that echinococcosis in this species is still related to the classic dog-sheep cycle, mainly diffused in Southern and Central Italy (Guberti et al 1993(Guberti et al , 2004. More recently, Gori et al (2015) recorded a lower occurence of E. granulosus (5.6%), analysing by polymerase chain reaction (PCR) and sequencing faecal samples of wolves from Liguria region.…”
Section: : 3% Of 109 Foxes)mentioning
confidence: 99%